O ensino de biologia mediado por Libras: perspectivas de licenciandos em ciências biológicas - Gomes, Paulo César [UNESP]; Basso, Sabrina Pereira Soares [UNESP] (My University, 2014)
Based on a study published by Souza and Silveira in 2011, this study aimed to investigate conceptions of undergraduates in the last year of a Biology course about the inclusion of deaf students in biology classes using Brazilian sign language – LIBRAS. Data were collected by means of a self-administered questionnaire, and analyzed with Qualitative Research Methods. From the analysis, it was found a large gap between, on the one hand, what literature provides as adaptations of biology education for deaf students and on the other hand, how be same teaching biology is understood. The data suggest that students have different understandings of the process of inclusion of deaf students in biology classes and how to program changes in the usual biology class style.

A partir de um estudo publicado por Souza e Silveira em 2011, este estudo buscou investigar as concepções de licenciandas do último ano de um curso de ciências biológicas acerca da inclusão do aluno surdo em aulas de biologia mediada pela linguagem brasileira de sinais – Libras. Os dados foram obtidos por meio de um questionário autoadministrado e analisado com base em premissas de uma Pesquisa Qualitativa. Da análise, verificou-se um grande distanciamento entre, de um lado, o que a literatura prevê como adaptações do ensino de biologia para os alunos surdos e, de outro, como este mesmo ensino de biologia é compreendido pelas estudantes. Os dados sugerem que as licenciandas têm distintas compreensões de como se dá o processo de inclusão do aluno surdo, o ensino de biologia para estes e mesmo em como programar mudanças no que elas priorizaram como modelo de aula expositiva habitual.
Teaching biology mediated by Brazilian Sign Language (Libras): perspectives of undergraduates biological sciences students
Keywords: Biology teacher; Signal Brazilian Language – LIBRAS; Inclusive education; Ensino de biologia; Libras; Inclusão escolar